Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve for [tex]\((f + g)(2)\)[/tex] given the functions [tex]\( f(x) = 2x^2 + 3x \)[/tex] and [tex]\( g(x) = x - 2 \)[/tex], follow these steps:
1. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 2(2)^2 + 3(2) \][/tex]
- Calculate [tex]\( (2)^2 \)[/tex]:
[tex]\[ 2^2 = 4 \][/tex]
- Multiply this by 2:
[tex]\[ 2 \times 4 = 8 \][/tex]
- Multiply 3 by 2:
[tex]\[ 3 \times 2 = 6 \][/tex]
- Add both results:
[tex]\[ 8 + 6 = 14 \][/tex]
Therefore, [tex]\( f(2) = 14 \)[/tex].
2. Evaluate [tex]\( g(x) \)[/tex] at [tex]\( x = 2 \)[/tex]:
[tex]\[ g(2) = 2 - 2 \][/tex]
- Subtract 2 from 2:
[tex]\[ 2 - 2 = 0 \][/tex]
Therefore, [tex]\( g(2) = 0 \)[/tex].
3. Add [tex]\( f(2) \)[/tex] and [tex]\( g(2) \)[/tex]:
[tex]\[ (f + g)(2) = f(2) + g(2) \][/tex]
- Substitute [tex]\( f(2) \)[/tex] and [tex]\( g(2) \)[/tex]:
[tex]\[ (f + g)(2) = 14 + 0 \][/tex]
- Add the results:
[tex]\[ 14 + 0 = 14 \][/tex]
Therefore, [tex]\((f + g)(2) = 14\)[/tex].
The correct answer is not provided directly among the options, but the result of [tex]\((f + g)(2)\)[/tex] is [tex]\(\boxed{14}\)[/tex].
1. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 2(2)^2 + 3(2) \][/tex]
- Calculate [tex]\( (2)^2 \)[/tex]:
[tex]\[ 2^2 = 4 \][/tex]
- Multiply this by 2:
[tex]\[ 2 \times 4 = 8 \][/tex]
- Multiply 3 by 2:
[tex]\[ 3 \times 2 = 6 \][/tex]
- Add both results:
[tex]\[ 8 + 6 = 14 \][/tex]
Therefore, [tex]\( f(2) = 14 \)[/tex].
2. Evaluate [tex]\( g(x) \)[/tex] at [tex]\( x = 2 \)[/tex]:
[tex]\[ g(2) = 2 - 2 \][/tex]
- Subtract 2 from 2:
[tex]\[ 2 - 2 = 0 \][/tex]
Therefore, [tex]\( g(2) = 0 \)[/tex].
3. Add [tex]\( f(2) \)[/tex] and [tex]\( g(2) \)[/tex]:
[tex]\[ (f + g)(2) = f(2) + g(2) \][/tex]
- Substitute [tex]\( f(2) \)[/tex] and [tex]\( g(2) \)[/tex]:
[tex]\[ (f + g)(2) = 14 + 0 \][/tex]
- Add the results:
[tex]\[ 14 + 0 = 14 \][/tex]
Therefore, [tex]\((f + g)(2) = 14\)[/tex].
The correct answer is not provided directly among the options, but the result of [tex]\((f + g)(2)\)[/tex] is [tex]\(\boxed{14}\)[/tex].
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.